O uso das variantes /ãũ/ ~ /õũ/ ~ /õ/ na fala da comunidade rio Guajará de Beja: uma abordagem sociolingüística - CARVALHO, Joseane Monteiro de (2023)
The present research (TCC) eith the title the use of variants /ãũ/~/ õũ /~/õ/ in the speech of rio Guajará de Beja`s community: an approach social linguistic was made in the community rio Guajará de Beja, islands region (archipelazo) of Abaetetuba`s city-PA, in the period frommarch to july of 2007. it presents a descriptive linguistic of qualitative nature analisy of the use of variants /ãũ/~/õũ/~/õ/ present in the speech of the people who live in this community in rio Guajará de Beja, under the optic methodolozy-theoric of variacionist social linguistic. in this perspective, we begin of pressupost that the linguistic factor the quantitative of syllables, and the position o variant in the word like the factors of the question, so as the work says (1990), phenomenon of the linguistic variation is relationate not only in linguistic questios, but also the characteristcs and social confiziration of each community whish speaks. Besides the linguistics values in what concern the description of the spoken Portuguese in the “insland” zones to contribute in historical and cultural terms, once that rescues the community` s history and culture researched in rio Guajara de Beja, wich is not registraded in the Abaetetuba`s rezion. Phenomenon studied here, was made in the residence of the informants, throuzh informal interviews with four men and four women, with the total of 08 informants, from the community rio Guajará de Beja, Abaetetuba city-PA. It was verificated through the analyses of the informations that the linguistic variarible quantitative of syllables and phonetic environment (neizhoor sounds) it doesn`t condition the use of the reffering variants /ãũ/~/õũ/~/õ/ wich is located in the variants in the word and tonicity of the syllable condition the using of the reffering variants. From the social variable studied, we observe that only the social factors school level and sex constitute in factors that condition the carryng out of variants /ãũ/~/õũ/~/õ/.